Efficacy and Safety of Salmeterol/fluticasone Combination Therapy in Infants and Preschool Children with Asthma Insufficiently Controlled by Inhaled Corticosteroids - Yoshihara, S.; Fukuda, H.; Tamura, M.; Arisaka, O.; Ikeda, M.; Fukuda, N.; Tsuji, T.; Hasegawa, S.; Kanno, N.; Teraoka, M.; Wakiguchi, H.; Aoki, Y.; Igarashi, H.; Terada, A.; Hasegawa, M.; Manki, A. (Drug Research, 2016)
Background: Clinical evidences of inhaled salmeterol/fluticasone propionate combination (SFC) therapy are insufficient in early childhood asthma.Objectives: To examine the effects of SFC50, a combination product of salmeterol xinafoate (50 μg/day) and fluticasone propionate (100 μg/day), in infants and preschool children with asthma.Methods: The study was conducted at 31 sites in Japan. 35 patients (6 months to 5 years old) with asthma insufficiently controlled by inhaled corticosteroids (100 μg/day) were initiated to treat with SFC50 twice a day for 12 weeks with pressurized metered dose inhalers. The efficacy of SFC50 was assessed using nighttime sleep disorder score as the primary endpoint and the other efficacy measurements. The safety measurement included the incidences of adverse event (AE).Results: Mean patient age was 3.1 years, and 94.2% had mild-to-moderate persistent asthma (atopic type: 65.7%). Nighttime sleep disorder scores, assessed by a nighttime sleep diary, significantly decreased after treatment with SFC50 throughout the study period (p<0.01). SFC50 also significantly improved other efficacy outcomes including asthma symptom score, frequency of short-acting beta-agonist treatment, frequency of unscheduled visits to clinic, frequency of exacerbation due to virus infection, asthma control score and patient QOL score (p<0.01). AEs of cold, upper respiratory inflammation and asthmatic attack occurred in each of the 3 patients (8.6%); however, these were not regarded as treatment-related AEs.Conclusions: SFC50 improved nighttime sleep disorder score and other efficacy outcome measures with no safety concerns. The results suggest that SFC50 treatment is useful to control the mild-to-moderate asthma in infant and preschool-aged children.
Keywords: salmeterol/fluticasone combination; asthma; infant; preschool children; nighttime sleep disorder score; long-acting beta-agonist; inhaled corticosteroid